Efecto de carryover de fomesafem sobre trigo, sorgo, maíz y girasol - Montoya, Jorgelina Ceferina; Ustarroz, Diego; Porfiri, Carolina; Schneider, Sharon; Gili, Adriana (Asociación Argentina de Ciencia de las Malezas, 2021)
Poster